Serenoa Repens (Saw Palmetto) for Lower Urinary Tract Symptoms (LUTS): The Evidence for Efficacy and Safety of Lipidosterolic Extracts. Part III - Stephen B. Strum (Uro, 2021)
Parts I and II of this three-part series indicated how a global review of both English-language and non-English language papers, plus a focus on a lipidosterolic extract of Serenoa repens (LSESr) having a standardized fatty acid profile, have together engendered new insights about the biological activity of LSESr vs. LUTS. In this last part, data from the world literature is presented that confirms that LSESr efficacy is the predominant finding in clinical trials. Despite two placebo-controlled clinical trials performed in the U.S. that failed to confirm a benefit of LSESr vs. placebo in LUTS, the global body of the peer-reviewed literature attests not only to efficacy but also to safety. Results will be presented of important trials that compare LSESr to alpha-blockers such as tamsulosin (Flomax®) as well as to 5α-reductase inhibitors such as finasteride (Proscar®) that demonstrate consistent findings of near equivalency between LSESr and these pharmacologic agents. Studies relating data indicative of an additive effect or synergy between LSESr and tamsulosin will also be presented. The heightened effectiveness of LSESr in men with severe LUTS vs. moderate LUTS expands the importance of our scrutiny of the global literature concerning LSESr. Of great consequence are the contributions of non-English language peer-reviewed publications that have consistently provided evidence of LSESr efficacy in treating LUTS/BPH. These peer-reviewed articles have shown that the effect of LSESr is not that of a placebo. Finally, a comparison of the LSESr extraction products used in the treatment of LUTS, and a discussion of the milieu factors that affect the natural history of LUTS and influence the outcome of clinical trials, complete this detailed analysis of LSESr vs. LUTS.